IP Spoofing & Its Detection Techniques for the Prevention of DOS Attacks - Hafeez , Hinna; Khalil, Tayyaba (Recent Progress in Science and Technology Vol. 6, 2023)
The lack of authentication allows the host machines to spoof the IP address of targeted machine [1], this can allow the host machine to use the targeted machine for mean purposes or can use the resources of targeted machine. The targeted machine can be used as zombie machine and can be used for DDOS/DOS attacks. That’s why there is a need to secure IP addresses of all the machines communicated on any network.